Influence of Technological Parameters on Ageing of Aluminium Alloy AW-2024 - Sobotka, Jiri; Solfronk, Pavel; Kolnerova, Michaela; Korecek, David (Manufacturing Technology Journal, 2018)
Right after the ferrous alloys, aluminium alloys represent the most wide spread used constructional materials of these days. The main reason of such utilization rests mainly in their specific weight, availability, good mechanical properties and corrosion resistance. To enhance their mechanical properties is there, at majority of technically used aluminium alloys, applied thermal treatment. Wrought aluminium alloys are generally processed after the solution annealing and before their natural or artificial hardening. However, in light of the formability is the own ageing process quite undesirable due to strong decrease of the material formability properties. In this paper is evaluated the time change of the aluminium alloy AW-2024 mechanical properties after the solution annealing in dependence on different storage time before forming. Such change of the mechanical properties was evaluated by means of the static tensile test.
Keywords: Aluminium Alloy AW-2024; Hardening; Solution Heat Treatment; Static Tensile Test; Formability